Exploitation of child labour: in search of leisure culture within the region of sugar cane in northeastern Brazil. - Mauricio Roberto da Silva (Universidade Federal de Santa Catarina, 2008)
This research brings to the debate the issue and interdisciplinary muldimensional of "exploitation of child labour", whose first goal is: "investigate within the exploitation of child labour, the world's leisure culture of working children, impoverished and exploited the Zona da Mata sugar Pernambuco, located in northeastern Brazil". In that sense, it is proposed the following question: "the logic of capitalist exploitation, with all its destructive load of work sold, managed to remove all or part time 'free' children to the enjoyment of leisure culture". After some reflections, seeks to make some relationships between work, body, "free time" and leisure in childhood and finally, some reservations about the play of these children in the spaces and times that are possible.